OIL SPILL TRAJECTORY SIMULATION AND ENVIRONMENTAL SENSITIVITY INDEX MAPPING : A CASE STUDY OF TANJUNG PRIOK, JAKARTA - Fuad, M. Arif Zainul (Directorate of Research and Community Service (DRPM), 2021)
Potential oil spills can be sourced from ship collisions, offshore oil drilling leaks, or refueling activities between ships. Tanjung Priok Port, Jakarta as the busiest port in Indonesia has the possibility of an oil spill disaster. Fuel oil could pollute the environment both in coastal and marine areas. As an anticipatory step, it is necessary to carry out an oil spill modeling simulation for contingency planning. Oil spill modeling was carried out using GNOME software using wind and ocean currents data as universal movers that move oil in the waters. The scenario used in this study is a spill occurred in March, the spill occurred during refueling between ships as much as 1500 barrels. The simulation results show that dominant oil spreads to the east and northeast and can reach sensitive areas in less than 4 days. Environmental sensitivity index mapping is carried out in areas that are predicted to be affected by an oil spill using ESI guidance from IPIECA. ESI map shows that the research area can be categorized into 5 categories from less sensitive (1B) to very sensitive (10A). Sensitive area is an intertidal area which is a habitat for mangroves and aquaculture.